Safety, bioavailability, and pharmacokinetics of VGX‐1027—A novel oral anti‐inflammatory drug in healthy human subjects. Issue 2 (8th June 2015) - Lee, Jessica C.; Menacherry, Stanley; Diehl, Malissa C.; Giffear, Mary D.; White, C. Jo; Juba, Rob; Bagarazzi, Mark L.; Muthumani, Karuppiah; Boyer, Jean; Agarwal, Vipin; Nicoletti, Ferdinando; Bart, Stephen; et al.
Abstract: VGX‐1027, a novel oral immune modulator, is under development for the treatment of rheumatoid arthritis. The safety, tolerability, and pharmacokinetics of single (1–800 mg) and multiple (40–400 mg) oral doses were evaluated in 2 clinical studies. The doses were well tolerated up to 800 mg in a single dose and 200 mg twice daily in multiple doses. Adverse events were mild to moderate in severity with no identifiable dose‐related pattern. There were no clinically significant physical or laboratory findings. The pharmacokinetic data indicated that increases in Cmax and AUC0−inf were dose‐proportional, and AUC0− τ was approximately dose‐proportional. For the single‐dose study, median Tmax ranged from 0.5 to 2 hours and mean t1/2 ranged from 4.9 to 8.7 hours. For the multiple‐dose study, median Tmax ranged from 0.5 to 2.0 hours and mean t1/2 ranged from 7.05 to 10.05 hours. No accumulation of the drug was observed after day 1, indicating that steady‐state concentrations were attained with single and multiple dosing for 5 days. Approximately 90% of the administered dose was excreted in urine as unchanged drug.